Investigating the role of social networking sites in increasing purchase intention for environmentally sustainable apparel: an exploratory study - Reiter, Lauren (Kansas State University, 2015)
With apparel production finding itself a leading cause of harm to the environment, the call to action to influence purchase intention for environmentally sustainable apparel (ESA) is pertinent for the current and future well-being of both the environment and humankind. Supplying a base of knowledge to consumers is crucial to enable them to understand the consequences the AT industry has on the environment. This knowledge can potentially lead to a change of attitude and change in purchase intention. However, reaching the populous and changing consumer knowledge of and attitudes towards environmentally sustainable apparel is challenging. This study considers social networking sites (SNS) a feasible strategy regarding this issue because they not only rapidly communicate to consumers but SNS also convey the attitudes and opinions of users’ online referent groups. This study better understands the variances among consumer characteristics and their knowledge of environmental issues in the apparel and textile industry. The purpose of this exploratory study is to initiate the investigation as to whether or not SNS may be a potential mechanism for increasing purchase intention for environmentally sustainable apparel. This exploration focuses on identifying consumer characteristics of social networking site users and investigating whether differences in consumer knowledge about environmental issues in apparel production leads to differences in attitudes about and ultimately purchase intentions of ESA. This study also examines whether or not the presence of social influence on SNS may serve as a mechanism to overcome the barriers (knowledge and attitudes) limiting purchase intention for ESA. An online national survey of 783 participants was conducted utilizing six scales. Simple bivariate correlations, ANOVA, and a hierarchial regression was conducted to understand if adding social influence of SNS as an additional component to Theory of Reasoned Action (TRA) provides greater predictive power for ESA behavior intentions. Findings from the study indicate that SNS influence and subjective norm are not stronger predictors of ESA purchase intention above knowledge and attitudes but they do contribute to the TRA and increasing the probability of purchase intention.
Keywords: Environmentally sustainable apparel; Social media; Consumer behavior; Purchase intention; Apparel; Marketing; Marketing (0338)